Program Penyediaan Air Minum Dan Sanitasi Di Kecamatan Tomoni Kabupaten Luwu Timur - Serniati, Epi Indah; Parawangi, Anwar; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine the evaluation of drinking water supply and sanitation programs in Tomoni Subdistrict, East Luwu Regency. This study used a descriptive qualitative research which tried to describe the environmental objective situation in the Timoni sub-district with its research informants as many as six (6) people. Data collection technique used observations, interviews, with a number of informants including sub-district staff, staff of the Public Works Office (PU), staff from the Health Office, water supply company staff, Tomoni sub-district village officials, and the community. The technique of checking the validity of the data used triangulation or method. Data analysis technique used interactive analysis. The results of this study showed that an evaluation of the water supply and sanitation program in Tomoni Subdistrict, East Luwu Regency had been effective, this was evidenced by the implementation of the Pamsimas program in most villages and sub-districts in the Timoni sub-district. But in the implementation there were certainly some obstacles or inhibiting factors: community awareness in maintaining facilities or tools that had been provided by the government, such as; toilets, water pipes, pipelines, water meters and others.